Strong and \(Δ\)-Convergence Results for Generalized Nonexpansive Mapping in Hyperbolic Space - Dashputre, Samir; Padmavati, C.; Sakure, Kavita (Communications in Mathematics and Applications, 2020)
In this paper, we propose a new iteration process which is faster than Picard Normal S-iteration process, Normal S-iteration process, Mann iteration process and Picard iteration process in hyperbolic space for generalized nonexpansive mapping. We also present strong and \(Δ\)-convergence results for proposed iteration process. An illustrative example with different set of parameters is also given in this paper.